2008
DOI: 10.1007/s11095-008-9751-8
|View full text |Cite|
|
Sign up to set email alerts
|

Movement of Heparins Across Rat Gastric Mucosa is Dependent on Molecular Weight and pH

Abstract: Decreasing heparin size, increases movement through gastric mucosa at mucosal buffer pH 7.4 but not pH 4.0. The stomach environment may favor UFH absorption while the intestine environment favors LMWH absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This suggests that UFH may be best absorbed in the stomach, while LMWH may be best absorbed in the intestine where a much larger absorptive surface is available and LMWH may be absorbed faster or more completely. 22 Thus, the present studies indicate that orally administered heparins, both UFH and LMWH, are effective antithrombotic agents in both rat arterial and venous models and can be given in repetitive doses without bleeding. Oral administration produces a similar antithrombotic effect as seen with subcutaneous administration, supporting the notion that orally administered heparins are readily absorbed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This suggests that UFH may be best absorbed in the stomach, while LMWH may be best absorbed in the intestine where a much larger absorptive surface is available and LMWH may be absorbed faster or more completely. 22 Thus, the present studies indicate that orally administered heparins, both UFH and LMWH, are effective antithrombotic agents in both rat arterial and venous models and can be given in repetitive doses without bleeding. Oral administration produces a similar antithrombotic effect as seen with subcutaneous administration, supporting the notion that orally administered heparins are readily absorbed.…”
Section: Discussionmentioning
confidence: 52%
“…This suggests that UFH may be best absorbed in the stomach, while LMWH may be best absorbed in the intestine where a much larger absorptive surface is available and LMWH may be absorbed faster or more completely. 22…”
Section: Discussionmentioning
confidence: 99%
“…There are several lines of evidence supporting the possibility of oral absorption of heparin. Hiebert et al (39,40) demonstrated that heparin could be permeated through the gastric mucosal membrane, and the repeated dose of oral UFH could show sufficient antithrombotic effects similar to subcutaneous administration. However, due to its hydrophilicity and negative charge density, heparin has limited intestinal membrane permeability.…”
Section: Discussionmentioning
confidence: 99%